Percursos da geografia escolar, de sua gênese às propostas curriculares organizadas por competências: em questão, a análise do Referencial Curricular de Geografia para o ensino fundamental (2ª fase) do estado do Tocantins - Gonçalves, Juliano Rosa (2010)
This work is an object of curriculum analysis prepared and implemented by the State of Tocantins to the state public education (Referencial Curricular). Therefore, the research considered the historical situation of creation and maintenance of a geographical knowledge in school, and the contextualization the new ideas that have appeared recently in the curriculum reforms. Thus, it is assumed that a panel designed to document analysis. The Referencial Curricular reflected the changes that are occurring in global and national contexts. Education reforms that broke the world at the transition of XX / XXI centuries had centrality in the curriculum. The Parâmetros Curriculares Nacionais (PCN) in Brazil corresponded with the movement of the reorganization of school function. The PCN influenced the development of state and local proposals. In Tocantins wasn t different. Replicating the same difficulties of theoretical and operational Parameters, the regional document just helped in the articulation of a geographical coherent narrative. By the way, there wasn t option declared: it was not admitted as entered in the traditional geography, or critical, or humanist or any other - although, overall, the document presented more characteristics of the first. The proposal to renew the teaching practice through competencies and abilities remained merely at the level of intention, because there wasn t distinction between what would be the competencies and abilities, and teaching procedures. This is a reflection the theoretical inconsistency in the document, and the application of teaching competencies in the Geography Education. Competencies that, due to its plasticity conceptual should be taken with care and clarity, to present the potential and the risks involved in adopting them on a curriculum. As balance, the results are not encouraging, since the confusion of epistemological and teaching are striking throughout the document